2022
DOI: 10.3390/jof8101003
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in Two Populations with Different Socioeconomic Resources in an Urban Nucleus: A Cross-Sectional Study

Abstract: Onychomycosis is one of the most common foot conditions. Mixed onychomycosis and onychomycosis caused by non-dermatophyte moulds are increasing in incidence, especially in vulnerable populations, hence the importance of this study, which presents the prevalence of onychomycosis in a population of homeless people, comparing the findings with a sample of a well-resourced population. The total sample consisted of 70 participants, divided into two separate groups, a homeless population and a second group in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…with a Rhodotorula spp. [22]. It is worth mentioning that R. similis was not identified from nail scales in any of these cases.…”
Section: Introductionmentioning
confidence: 74%
“…with a Rhodotorula spp. [22]. It is worth mentioning that R. similis was not identified from nail scales in any of these cases.…”
Section: Introductionmentioning
confidence: 74%
“…Sufficient data were available to compare the prevalence of NDM onychomycosis in clinically suspected patients who underwent single ( n = 81,515) or repeat sampling ( n = 32,171) 16,50–112 . Across both Global North and Global South regions, results from studies where single sampling is performed showed a higher degree of variability compared to studies that utilized the recommended repeat sampling approach (Figure 3).…”
Section: Resultsmentioning
confidence: 99%